2012
DOI: 10.1007/s10646-012-0921-4
|View full text |Cite
|
Sign up to set email alerts
|

The influence of external subsidies on diet, growth and Hg concentrations of freshwater sport fish: implications for management and fish consumption advisories

Abstract: Mercury (Hg) contamination in sport fish is a global problem. In freshwater systems, food web structure, sport fish sex, size, diet and growth rates influence Hg bioaccumulation. Fish stocking is a common management practice worldwide that can introduce external energy and contaminants into freshwater systems. Thus, stocking can alter many of the factors that influence Hg concentrations in sport fish. Here we evaluated the influence of external subsidies, in the form of hatchery-raised rainbow trout Oncorhynch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…Sexual dimorphism may be linked to differences in muscle-Hg concentrations for some species (Lepak et al, 2012). Additionally, sex-related metabolic differences in growth and behavior may also affect Hg metabolism and bioaccumulation (Henderson et al, 2003;McClain et al, 2006;Rennie et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Sexual dimorphism may be linked to differences in muscle-Hg concentrations for some species (Lepak et al, 2012). Additionally, sex-related metabolic differences in growth and behavior may also affect Hg metabolism and bioaccumulation (Henderson et al, 2003;McClain et al, 2006;Rennie et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Esocids (Marwitz and Hubert 1997, Flinders and Bonar 2008, Lepak et al 2012a, 2012c and other piscivores like walleye (Sander vitreus; Yule et al 2000, Baldwin et al 2003, Lepak et al 2012b) are consuming stocked fish, which is expected given that hatchery-reared fish have relatively limited experience with predators (Suboski and Temple ton 1989, Brown and Smith 1998, Ferrari et al 2010). …”
Section: Predation On Stocked Salmonidsmentioning
confidence: 99%
“…For example, rainbow trout (Oncorhynchus mykiss) are stocked widely (Halverson 2010), but even rainbow trout >150 mm are consumed by piscivores (Yule et al 2000, Lepak et al 2012b). Kekäläinen et al (2008) found that a population of ∼1500 northern pike (Esox lucius) >40 cm consumed ∼29% of 40,000 stocked Atlantic salmon (Salmo salar) smolts in a 2.5 km reach of a northern Baltic river over the course of 7 d. In addition, introduced nonnative piscivores are frequently related to declines in native fish populations (Findlay et al 2000, Muhlfeld et al 2008, and native fish restoration efforts can be hindered when nonnative piscivores consume stocked native fish (Karam and Marsh 2010).…”
mentioning
confidence: 99%
“…On the basis of the assumption that a cell has a spherical shape, its weight is proportional to the cube of the length. Thus, the cells’ growth expressed by the increase in their weight, and the ratio between the mass of cells (or fish weight) exposed to a certain chemical concentration and the mass of cells (or fish weight) in the control sample, can be described by the following equations ( 43 ): where W ( t ) is weight (mg) at time t (day), W ∞ is the theoretical maximum weight (asymptotic, mg), K is a growth coefficient (1/day), and t 0 is the theoretical age (day) at W = 0.…”
Section: Methodsmentioning
confidence: 99%